2014
DOI: 10.1111/mmi.12824
|View full text |Cite
|
Sign up to set email alerts
|

Nucleo‐cytoplasmic shuttling dynamics of the transcriptional regulators XYR1 and CRE1 under conditions of cellulase and xylanase gene expression in Trichoderma reesei

Abstract: Trichoderma reesei is a model for investigating the regulation of (hemi-)cellulase gene expression. Cellulases are formed adaptively, and the transcriptional activator XYR1 and the carbon catabolite repressor CRE1 are main regulators of their expression. We quantified the nucleo-cytoplasmic shuttling dynamics of GFP-fusion proteins of both transcription factors under cellulase and xylanase inducing conditions, and correlated their nuclear presence/absence with transcriptional changes. We also compared their su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 80 publications
(98 reference statements)
8
79
0
3
Order By: Relevance
“…Recently, it was observed that CRE1 in T. reesei does not require de novo biosynthesis and is imported into the nucleus from a preformed cytoplasmic pool (Lichius et al 2014). Microscopy was carried out on A. nidulans CreA::GFP germlings, where the creA (AN6195 ) wild-type allele was replaced with the creA::gfp allele (strain TN02a3) (Table S1) (Brown et al 2013), grown for 16 hr in glucose (CreA target genes repressed; CreA localizes to the nucleus), and then transferred to Xylan for 6 hr (CreA target genes derepressed; CreA leaves the nucleus) before glucose was added to the Xylan cultures for 30 min (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was observed that CRE1 in T. reesei does not require de novo biosynthesis and is imported into the nucleus from a preformed cytoplasmic pool (Lichius et al 2014). Microscopy was carried out on A. nidulans CreA::GFP germlings, where the creA (AN6195 ) wild-type allele was replaced with the creA::gfp allele (strain TN02a3) (Table S1) (Brown et al 2013), grown for 16 hr in glucose (CreA target genes repressed; CreA localizes to the nucleus), and then transferred to Xylan for 6 hr (CreA target genes derepressed; CreA leaves the nucleus) before glucose was added to the Xylan cultures for 30 min (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The regulation of CreA/CRE1/CRE-1 appears to be at least partially dependent on intracellular localization. Under repressing conditions, CreA/CRE1/CRE-1 is found in the nucleus where it can regulate the expression of target genes, and when under de-repressing conditions, CreA/CRE1/CRE-1 exits the nucleus (Brown et al, 2013;Cupertino et al, 2015;Lichius et al, 2014). However, the genetic regulation of CreA/CRE1/CRE-1 appears to be fairly divergent amongst the filamentous fungi.…”
mentioning
confidence: 99%
“…In filamentous fungi, CCR is mediated by the CreA/CRE1 protein [28], which is a functional homologue of Mig1p. CreA/CRE1 is localized in the cytoplasm under non-repressing conditions and is shuttled to the nucleus under repressing conditions [37,38]. Its localization is regulated by its phosphorylation state [37], similar to Mig1p.…”
Section: Signalling Cascades Related To Nutrient Sensing and Expressimentioning
confidence: 99%
“…Section I described how some of the inducers of CAZymes are different in T. reesei compared to A. niger, namely the effects of lactose and sophorose, but these different inducers can still signal through the XYR1 transcription factor in T. reesei. Measurements of the shuttling of XYR1 in T. reesei provide insights into the functioning of this activator [38]. The XYR1 protein was synthesised in the cytoplasm as part of the induction process and when induction ceased the XYR1 protein in the nucleus was rapidly degraded [38].…”
Section: Xlnr/xyr1 Activators In Aspergillus Spp and T Reeseimentioning
confidence: 99%
See 1 more Smart Citation